Open Access ArticleGo Back Image Steganography for Message Hiding Using Genetic Algorithm - Gaidhani, Chaitali R; Deshpande, Vedashree M; Bora, Vrushali N (International Journal of Computer Sciences and Engineering, 2014)
Considering the need for higher security in Secrete Message transmission we introduce Image Steganography for Message Hiding Using Genetic Algorithm. We are going to propose a system in which we can share a secrete message without letting anyone know the presence of that message behind any sample image, this term is called Steganography. To make it more powerful and secure than before we are introducing Genetic Algorithm in this technique.